SCHOOL TRAJECTORIES OF YOUNG PEOPLE IN ILLITERACY SITUATIONS: INVISIBILITY, DROPOUTS AND PERSISTENCE - Russano, Paola Fonseca [UNESP]; Prioste, Claudia [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2024)
: Literacy at all stages of life is a human right that promotes improving living conditions. This research aimed to understand the difficulties faced by illiterate young people in schooling. This qualitative and documentary research was carried out through analysis of school records and interviews with young students and their teachers in a Youth and Adult Education (EJA) school. The results indicate fragmented paths marked by failures in schooling, evasions, and some persistence. EJA represents hope for literacy achievement, work, and social inclusion. However, staying there is challenging due to learning difficulties; social vulnerabilities intensified by violent contexts; mental health disorders; drug abuse; early pregnancy, and overload in the working day. It was concluded that it is essential to offer psychosocial support and formal literacy spaces at all school stages, with strategies that contribute to access to the job market, autonomy, and citizenship.
Keywords: Youth and Adult Education; Illiteracy; Youth; School education; School Failur & edot;